2022
DOI: 10.1126/sciadv.abm4950
|View full text |Cite
|
Sign up to set email alerts
|

Genomic consequences of domestication of the Siamese fighting fish

Abstract: Siamese fighting (betta) fish are among the most popular and morphologically diverse pet fish, but the genetic bases of their domestication and phenotypic diversification are largely unknown. We assembled de novo the genome of a wild Betta splendens and whole-genome sequenced 98 individuals across five closely related species. We find evidence of bidirectional hybridization between domesticated ornamental betta and other wild Betta species. We discover … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 112 publications
4
52
0
Order By: Relevance
“…The primary genetic mechanisms of SDS in Siamese fighting fish remain poorly understood. Recent studies revealed that Siamese fighting fish in one commercial stock have an XX/XY SDS [ 13 ], while the dmrt1 gene might be a candidate for sex determination [ 13 , 14 ]. To extend our understanding of the SDS of Siamese fighting fish, we genotyped 75 offspring from five commercial populations at 23,509 loci (without filtering) derived from genome-wide SNPs distributed throughout the genome—on average, one every 18.79 kb.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The primary genetic mechanisms of SDS in Siamese fighting fish remain poorly understood. Recent studies revealed that Siamese fighting fish in one commercial stock have an XX/XY SDS [ 13 ], while the dmrt1 gene might be a candidate for sex determination [ 13 , 14 ]. To extend our understanding of the SDS of Siamese fighting fish, we genotyped 75 offspring from five commercial populations at 23,509 loci (without filtering) derived from genome-wide SNPs distributed throughout the genome—on average, one every 18.79 kb.…”
Section: Discussionmentioning
confidence: 99%
“…Similar cases were also observed in Atlantic salmon ( Salmo salar Linnaeus, 1758 [ 85 ]) [ 86 ] and Nile tilapia ( Oreochromis niloticus Linnaeus, 1758 [ 87 ]) chromosomes [ 88 ] where sex-specific and sex-linked loci were distributed on the sex chromosomes. The highest repeat area richness of the Siamese fighting fish genome is BSP9, having more than twice the number of repeats than that of the other chromosomes [ 13 ]. Repetitive elements can mediate chromosomal rearrangements that further induce sex chromosome differentiation and heterochromatin propagation [ 3 , 89 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations